Inflation targeting regime on the example of the Bank of England - Černý, Ondřej (2022)
This thesis, called Inflation targeting regime on the example of the Bank of England, is focused on describing the theory behind inflation targeting as a framework for monetary policy, using the Bank of England as a specific example and assessment of this bank’s success. The first chapter introduces the background and the basic characteristics on which the regime is based. It then outlines its shortcomings, the unconventional tools associated with addressing these shortcomings, criticisms of the regime during the 2008 financial crisis, and comparisons with alternative regimes. The second chapter presents the implementation of the inflation targeting regime in the Bank of England's monetary policy, what preceded its adoption, and the evolution of the policy from adoption to the present. The third and smallest chapter of the thesis deals with the stationarity of the time series and its testing so that the time series can be used for analysis. The fourth chapter deals with analyzing the success in the United Kingdom. Graphical analysis is used, the development of inflation is described, and the reasons for not achieving the target are discussed. Correlation analysis is done for the official interest rate set by the Bank of England and market rates. These rates are further tested for correlation with lagged inflation over selected time horizons. The relationship between deviations from the inflation target and the deviations of the United Kingdom's gross domestic product from its potential is also examined. Finally, previous research on the effects of quantitative easing in the UK is summarized.